2011
DOI: 10.1007/s11655-011-0659-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based Rasayana drugs from Ayurveda

Abstract: Rasayana tantra is one of the eight specialties of Ayurveda. It is a specialized practice in the form of rejuvenative recipes, dietary regimen, special health promoting behaviour and drugs. Properly administered Rasayana can bestow the human being with several benefits like longevity, memory, intelligence, freedom from diseases, youthful age, excellence of luster, complexion and voice, optimum strength of physique and sense organs, respectability and brilliance. Various types of plant based Rasayana recipes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 26 publications
0
64
0
Order By: Relevance
“…In recent years, traditional medicines have been playing more and more important roles in the maintenance of health, the prevention and treatment of diseases, and plant-based drug discovery [48]. Chinese herbal medicine or its products have been administered widely for treating CHD in China.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, traditional medicines have been playing more and more important roles in the maintenance of health, the prevention and treatment of diseases, and plant-based drug discovery [48]. Chinese herbal medicine or its products have been administered widely for treating CHD in China.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is indicated that Rasayana drugs act through nutrition dynamics, for example, improving the quality of plasma (Rasa enhancing), normalizing the digestion and metabolism ( Agni ), and improving tissue perfusion of nutrients ( Srotas ) at molecular level. [37] This gap provides an opportunity for further research on Rasayanas at Dhatu level using stem cells.…”
Section: Ayurveda and Translational Stem Cells Research: Experimentalmentioning
confidence: 99%
“…Traditional literature describes Rasayanas as interventions that reverse naturally occurring senility and improve mental competence, increase immunity against diseases, provide vitality and luster to the body and increase longevity [2]. As Ayurveda, Rasayanas are supposed to act holistically on the body by (i) improving the process of digestion and metabolism (Agni), increasing bio-availability of nutrients, (ii) optimizing the micro-circulation of nutrients through the body channels (Srotas), and (iii) enhancing the nutritive value of the plasma that becomes re-generated (Rasadhatu) [3,4]. Natural products and herbal medicines are promising sources of new agents and interesting candidates for the development of complementary and alternative treatments to conventional drug regimens.…”
Section: Introductionmentioning
confidence: 99%